2014
DOI: 10.1016/j.ijdevneu.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine exposure during pregnancy at pharmacological doses produces neurodevelopmental and behavioural effects in rat offspring

Abstract: In recent years methamphetamine (MA) use has become more prevalent, and of particular concern is its growing popularity of MA among women of childbearing age. However, to date, studies examining MA effects on the developing offspring in laboratory animals are limited. Thus, the aim of this study was to determine if in utero MA exposure in rats at pharmacological doses can have a negative impact on neonatal neurodevelopment and behaviour. Pregnant Sprague-Dawley dams (n=10 dams/group) received MA (0, 0.625, 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
2
23
3
Order By: Relevance
“…This observation is in contrast to the human (Good et al, 2010; Smith et al, 2006) and rodent literature (Acuff-Smith et al, 1996, Cho et al, 1991, McDonnell-Dowling et al, 2014, 2015b, 2016) showing that METH use/administration during pregnancy can lead to inadequate weight gain seen in the present study. Multiple reasons could account for the similarities in weight gain.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This observation is in contrast to the human (Good et al, 2010; Smith et al, 2006) and rodent literature (Acuff-Smith et al, 1996, Cho et al, 1991, McDonnell-Dowling et al, 2014, 2015b, 2016) showing that METH use/administration during pregnancy can lead to inadequate weight gain seen in the present study. Multiple reasons could account for the similarities in weight gain.…”
Section: Discussioncontrasting
confidence: 99%
“…The latter results are in contrast to the human literature, where in utero METH-exposed newborns were found to be small for their gestational age (Minnes et al, 2012; Smith et al, 2003) and similar findings of decreased birthweight have been reported in other rodent studies (McDonnell-Dowling et al, 2014, 2015b; Slamberova et al, 2005). While this lack of difference can likely be explained by factors already described (e.g., daily dose, mode of administration, maternal health), it also suggests that moderate doses of METH throughout pregnancy, provided that it is self-administered, do not hinder appropriate growth and weight development of offspring after birth.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Although, previous studies have shown that EE reduced selfadministration and seeking behaviors of amphetamine and cocaine [11,12], MDMA (Ecstasy)-induced CPP [1]. Therefore, relatively low doses of oral METH in our study causes rewarding effects in the METH/SE rats, similar to human and animal studies [8,19]. In this study, the rats had free access to water and METH which preferred METH to water, reflecting an incentive demand for the drug in TBC model.…”
Section: Discussionmentioning
confidence: 49%